Software and Hardware Testing Platform for High Resolution ADCs - Shehzad, Ahsan (My University, 2013)
Performance evaluation of high resolution ADCs is a growing challenge in industry. This report describes a software and hardware testing platform for high resolution ADCs. It explains the requirements of a high resolution ADC under test. Requirements of signal to noise ratio (SNR) of input signal, requirements of allowed jitter on sampling clock and requirements of noise on the power supplies are explored. Noise from different sources like current noise, voltage noise and thermal noise are estimated for components of supply and then verified by implementation results. Signal integrity precautions affecting resolution are also explored and implemented.
Keywords: Data- och informationsvetenskap; Computer and Information Science